Dam displacement resettlement and rehabilitation - Vachhani, Ashish (Mussoorie, 2009)
The present study is an attempt to explore a wide spectrum of issues including the socio- demographic profile of displaced people, the process of displacement, land acquisition, resettlement and rehabilitation and its socio-economic and cultural impact In the conclusion, it provides recommendations for policy makers.
Keywords: Tehri Dam-Rehabilitation